10-Year Follow-Up Results of The Netherlands Longitudinal Study on Hearing: Trends of Longitudinal Change in Speech Recognition in Noise. Issue 3 (May 2020) - Goderie, Thadé P. M.; Stam, Mariska; Lissenberg-Witte, Birgit I.; Merkus, Paul; Lemke, Ulrike; Smits, Cas; Kramer, Sophia E.
Abstract : Objectives: Previous findings of longitudinal cohort studies indicate that acceleration in age-related hearing decline may occur. Five-year follow-up data of the Netherlands Longitudinal Study on Hearing (NL-SH) showed that around the age of 50 years, the decline in speech recognition in noise accelerates compared with the change in hearing in younger participants. Other longitudinal studies confirm an accelerated loss in speech recognition in noise but mostly use older age groups as a reference. In the present study, we determined the change in speech recognition in noise over a period of 10 years in participants aged 18 to 70 years at baseline. We additionally investigated the effects of age, sex, educational level, history of tobacco smoking, and alcohol use on the decline of speech recognition in noise. Design: Baseline (T0), 5-year (T1), and 10-year (T2) follow-up data of the NL-SH collected until May 2017 were included. The NL-SH is a web-based prospective cohort study which started in 2006. Central to the NL-SH is the National Hearing test (NHT) which was administered to the participants at all three measurement rounds. The NHT uses three-digit sequences which are presented in a background of stationary noise. The listener is asked to enter the digits using the computer keyboard. The outcome of the NHT is the speech reception threshold in noise (SRT) (i.e., the signal to noise ratio where a listener recognizes 50% of the digit triplets correctly). In addition to the NHT, participants completed online questionnaires on demographic, lifestyle, and health-related characteristics at T0, T1, and T2. A linear mixed model was used for the analysis of longitudinal changes in SRT. Results: Data of 1349 participants were included. At the start of the study, the mean age of the participants was 45 years (SD 13 years) and 61% of the participants were categorized as having good hearing ability in noise. SRTs significantly increased (worsened) over 10 years ( p < 0.001). After adjustment for age, sex, and a history of tobacco smoking, the mean decline over 10 years was 0.89 dB signal to noise ratio. The decline in speech recognition in noise was significantly larger in groups aged 51 to 60 and 61 to 70 years compared with younger age groups (18 to 30, 31 to 40, and 41 to 50 years) ( p < 0.001). Speech recognition in noise in participants with a history of smoking declined significantly faster during the 10-year follow-up interval ( p = 0.003). Sex, educational level, and alcohol use did not appear to influence the decline of speech recognition in noise. Conclusions: This study indicated that speech recognition in noise declines significantly over a 10-year follow-up period in adults aged 18 to 70 years at baseline. It is the first longitudinal study with a 10-year follow-up to reveal that the increased rate of decline in speech recognition ability in noise already starts at the age of 50 years. Having a history of tobacco smoking increases the decline of speech recognition in noise. Hearing health care professionals should be aware of an accelerated decline of speech recognition in noise in adults aged 50 years and over.